Escherichia coli ST471 Producing VIM-4 Metallo-β-Lactamase in Colombia (2022)
ABSTRACT: An Escherichia coli isolate sequence-type 471 (ST471) producing Verona integron-encoded metallo-blactamases (VIM)-4 was recovered from a rectal swab in a patient without travel records with osteomyelitis in Colombia. The isolate carried a class 1 integron-borne blaVIM-4 gene with a 170-bp duplication in the 3' end of the gene, preceded by an aac(6¢)-Ib gene. The genetic environment of blaVIM-4, blaCMY-2, and sul2 genes showed similarities to the backbone of pKKp4, an IncA/C-type plasmid from a Klebsiella neumoniae strain carrying blaVIM-4 recovered in Kuwait. This is the first report of blaVIM-4 in Enterobacterales in South America. Our results suggest that blaVIM-4 gene was found on an IncA/C-type plasmid that could play a role in the spread of VIM-4 carbapenemase in Colombia.